Effect of Industry CompetÄ±tÄ±on and EntrepreneurÄ±al Company to ImplementatÄ±on of DÄ±fferentÄ±atÄ±on Strategy, SME Performance, and Poverty AllevÄ±atÄ±on - Yasa, Ni Nyoman Kerti; Sukaatmadja, Putu Gde; Rahyuda, Henny; Giantari, I.G.A Ketut (APMBA (Asia Pacific Management and Business Application), 2014)
The purpose of this study was to determine the effect intensity of industry competition and entrepreneurial company to the implementation of differentiation strategy, SME (Small and Medium Enterprise) performance, and poverty alleviation. In this study examined five variables, namely intensity of industry competition, entrepreneurial company, implementation of differentiation strategy, and SME performance, and poverty alleviation. This study took place in the Gianyar regency with target population of the SME industry. Sampling was purposive sampling study. Based on Slovin's formula, the number of samples taken was as many as 100 SME that spread across districts in Gianyar regency. Respondents were managers. Statistical analysis was used to test hypothesis is Structural Equation Model (SEM). The results showed that the intensity of industry competition has positive and significant effect on the implementation of differentiation strategy, and the intensity of industry competition has positive and significant effect on the performance of SME. Entrepreneurial company has positive and not significant effect on the implementation of differentiation strategy, and entrepreneurial company also has positive and not significant effect on the performance of SME, as well as the implementation of differentiation strategy has positive and significant effect on the performance of SME. Furthermore, SME performance improvement can enhance poverty alleviation in the Gianyar regency. And for the future, SME in Gianyar regency should be intensified to implement strategy of differentiation and increase entrepreneurial company in order to improve the performance of SME and their implications for poverty alleviation in Gianyar regency.